Higher baseline platelet and preoperative platelets to lymphocytes ratio was associated with a higher incidence of axillary node pathologic complete response after neoadjuvant chemotherapy in HER2-low breast cancer: a retrospective cohort study - Yang, Shuai; Liang, Guanying; Sun, Junyi; Yang, Lingbing; Fu, Zitong; Sun, Wantong; Wei, Bo; Nanding, Abiyasi; Wang, Qin; Xu, Shouping (Frontiers in Oncology, 2025)
BackgroundHER2 expression has a central role in breast cancer carcinogenesis and is associated with poor prognosis. Lately, identification of HER2-low breast cancer has been proposed to select patients for novel HER2-directed chemotherapy and includes cancers with immunohistochemistry (IHC) 1+or 2+with negative fluorescence in situ hybridization (FISH), encompassing approximately 55–60% of all breast carcinomas. Neoadjuvant chemotherapy(NAC) is an important therapeutic modality for HER2-low breast cancer (BC). Immune inflammatory biomarkers have been reportedly linked to the prognosis of some different breast cancer types, with varying results. In this study, we investigated the possible predictive roles of blood-based markers and clinicopathologic features in axillary pathologically complete response (pCR) after neoadjuvant treatment (NAT) in HER2-low BC.MethodsHER2-low BC patients diagnosed and treated in the Harbin Medical University Cancer Hospital from January 2012 to December 2018 were included. Relevant clinical and pathological characteristics were included, and baseline and preoperative complete blood cell counts were evaluated to calculate four systemic immune-inflammatory markers: neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-inflammation index (SII). The optimal cutoff values for these markers were determined using ROC curves and patients were classified into high-value and low-value groups based on these cutoff values. Univariate and multivariate logistic regression analyses were conducted to analyze factors influencing axillary pCR. The factors with independent predictive value were used to construct a forest map.ResultsA total of 998 patients were included in the study. 35.6% (355 of 998) of patients achieved axillary pCR after NAC. The result of multivariate logistic regression analysis showed that Estrogen receptor (ER) (OR=2.18; 95% CI 1.43-3.32; P<0.001),pathology type (OR=0.51; 95% CI 0.40-0.65; P<0.001),baseline platelet (OR=1.45; 95% CI 1.02-2.05; P=0.037),preoperative PLR (OR=1.63; 95% CI 1.01-2.64; P=0.046) were significant independent predictors of ypN0.ConclusionThe forest map for predicting axillary pCR incorporates four variables, including ER, pathology type, platelet, platelet-to-lymphocyte ratio (PLR). In patients treated with NAC, a higher baseline platelet and a higher preoperative PLR was associated with a higher incidence of axillary pCR.